2010
DOI: 10.1021/ja101192e
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Cationic Two-Coordinate Group-13 Ligand Systems by Spontaneous Halide Ejection: Remarkably Nucleophile-Resistant (Dimethylamino)borylene Complexes

Abstract: Spontaneous ejection of chloride from a three-coordinate boron Lewis acid can be effected by employing very electron rich metal substituents and leads to the formation of a sterically unprotected terminal (dimethylamino)borylene complex that has a short metal-boron bond and remarkable resistance to attack by nucleophilic and protic reagents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…The former is a 12‐electron Rh III fragment that binds arenes (e.g., fluorobenzene) in an η 6 ‐manner, whereas the latter is formally a 12‐electron Rh III centre with a supporting C–C σ‐bond and an agostic C–H interaction. Although the [BAr Cl2 4 ] – anion was originally reported in the open literature by Pacey as the Cs + salt,10 with a refinement in the synthesis by Serwatowski and co‐workers in 2003,11 as far as we are aware it has not been utilised in organometallic chemistry to generate and stabilise potentially reactive metal cations 12. We believe that this anion will be of use to the organometallic and catalysis communities as well as those interested in the structural determination of cationic species given its ease of preparation, attractive solubility properties, lack of anion disorder in the solid‐state, comparable coordinating properties to C 6 H 5 F and [BAr F 4 ] – , and its expedient use in synthesis.…”
Section: Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“…The former is a 12‐electron Rh III fragment that binds arenes (e.g., fluorobenzene) in an η 6 ‐manner, whereas the latter is formally a 12‐electron Rh III centre with a supporting C–C σ‐bond and an agostic C–H interaction. Although the [BAr Cl2 4 ] – anion was originally reported in the open literature by Pacey as the Cs + salt,10 with a refinement in the synthesis by Serwatowski and co‐workers in 2003,11 as far as we are aware it has not been utilised in organometallic chemistry to generate and stabilise potentially reactive metal cations 12. We believe that this anion will be of use to the organometallic and catalysis communities as well as those interested in the structural determination of cationic species given its ease of preparation, attractive solubility properties, lack of anion disorder in the solid‐state, comparable coordinating properties to C 6 H 5 F and [BAr F 4 ] – , and its expedient use in synthesis.…”
Section: Introductionmentioning
confidence: 56%
“…An approximate coordinating ability can also be established compared with [BAr F 4 ] – and C 6 H 5 F in which [BAr Cl2 4 ] – interacts with very open metal centres more strongly than [BAr F 4 ] – , but is competitive, although more strongly binding, with the weakly coordinating solvent C 6 H 5 F. With less available, albeit reactive, metal centres, e.g., 1 [BAr Cl2 4 ], the coordinating properties of the anions are levelled and neither interact. Indeed in this respect, [BAr Cl2 4 ] – has very recently been used in the isolation of a two‐coordinate‐at‐boron, 18‐valence‐electron, cationic, iron–borylene complex, in which these desirable properties of solubility, ease of synthesis and chemical robustness are further highlighted 12. Of course, in systems in which oxidative addition to a metal centre of aryl chlorides is a straightforward process,15 such as in cross‐coupling reactions,16 these anions might be of less use, although this offers potential opportunities for derivatisation of the anion itself.…”
Section: Discussionmentioning
confidence: 99%
“…Aldridge et al reported that oxidative addition of a B–H bond of dihydroaminoboranes H 2 BNR 2 (R = i Pr, Cy) to an iridium center and subsequent 1,2-hydride migration triggered by chloride abstraction from the iridium center resulted in the formation of cationic borylene complexes [ fac -Ir­(PMe 3 ) 3 (H) 2 (BNR 2 )]­[BAr F 4 ] . Aldridge et al also reported another approach to the synthesis of cationic borylene complexes [Cp*Fe­(CO) 2 (BMes)] + and [CpFe­(dmpe) 2 (BNMe 2 )] + through halide abstraction from the haloboryl complexes …”
Section: Introductionmentioning
confidence: 99%
“…The first bridging borylene complexes,3 as well as the only known terminal alkyl borylene complex,4 all partly owe their stability to the properties of the manganese fragment. In terms of transition metal borylene chemistry, twelve structurally characterized neutral terminal transition metal borylene complexes (Scheme )414 and nine terminal cationic transition metal borylene complexes (Scheme )1522 have been reported. Additionally, a number of base‐stabilized adducts formed by the coordination of a Lewis base (main group or transition metal) to the two‐ or three‐coordinate boron center have also been prepared.…”
Section: Introductionmentioning
confidence: 99%